List of Chinese Students Receiving a Ph.D. in Chemistry between 1905 and 1964 - Mainz, Vera (University of Illinois at Urbana-Champaign, 2017)
List of Chinese Students Receiving a Ph.D. in Chemistry between 1905 and 1964. Based on two books compiling doctoral dissertations by Chinese students in the United States. Includes disciplines; university; advisor; year degree awarded, birth and/or death date, dissertation title. Accompanies Chapter 5 : History of the Modern Chemistry Doctoral Program in Mainland China by Vera V. Mainz published in "Igniting the Chemical Ring of Fire : Historical Evolution of the Chemical Communities in the Countries of the Pacific Rim", Seth Rasmussen, Editor. Published by World Scientific. Expected publication 2017.
Keywords: Chinese; graduate student; dissertation; university; advisor; chemistry; engineering; materials science